2020
DOI: 10.1017/s1092852920000061
|View full text |Cite
|
Sign up to set email alerts
|

Toward a transdiagnostic neurocircuitry-based biomarker model for pro-cognitive effects: challenges, opportunities, and next steps

Abstract: Cognitive impairment has emerged as a key treatment priority in neuropsychiatric disorders. However, there is a lack of treatments with solid and lasting efficacy on cognition. A neurocircuitry-based biomarker model of pro-cognitive effects is critically needed to select among new candidate treatments. In a recent review of functional magnetic resonance imaging (fMRI) studies in mood disorders, we found that cognitive impairments are consistently accompanied by aberrant (hypo- and hyper-) activity in the dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Another explanation could be that the potent placebo response could have masked a possible beneficial effect of exenatide (Figure 3-4). The observed potent placebo response could be due to the standardized cognitive behaviour therapy (CBT) against AUD (38) offered to all participants in the study, but it could also be due to the less severity profile of the AUD patients included, which is typically linked to a higher placebo response (33). Large placebo responses are also reported in other clinical AUD trials and shown to be negatively correlated with the treatment intervention effect sizes (34).…”
Section: Discussionmentioning
confidence: 93%
“…Another explanation could be that the potent placebo response could have masked a possible beneficial effect of exenatide (Figure 3-4). The observed potent placebo response could be due to the standardized cognitive behaviour therapy (CBT) against AUD (38) offered to all participants in the study, but it could also be due to the less severity profile of the AUD patients included, which is typically linked to a higher placebo response (33). Large placebo responses are also reported in other clinical AUD trials and shown to be negatively correlated with the treatment intervention effect sizes (34).…”
Section: Discussionmentioning
confidence: 93%
“…Abnormal activity within the DMN is classically linked to increased rumination, but is also associated with impaired control of attention ( 54 ). Failing to reduce activation within the DMN whilst actively undertaking a cognitive task appears to directly relate to poor task performance, whereas appropriate “switching off” of the DMN during tasks is linked with improved cognitive performance ( 55 ). In this way, improving appropriate deactivation of the DMN during cognitive tasks has been proposed as a transdiagnostic marker to assess for pro-cognitive effects of interventions ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Failing to reduce activation within the DMN whilst actively undertaking a cognitive task appears to directly relate to poor task performance, whereas appropriate “switching off” of the DMN during tasks is linked with improved cognitive performance ( 55 ). In this way, improving appropriate deactivation of the DMN during cognitive tasks has been proposed as a transdiagnostic marker to assess for pro-cognitive effects of interventions ( 55 ). Therefore, the decreased activation of DMN-related regions during task performance in this fMRI faces task may reflect enhanced attention and cognitive control, which is consistent with the improvement in performance accuracy seen behaviourally.…”
Section: Discussionmentioning
confidence: 99%
“…The current study had several limitations to consider. First, although a transdiagnostic sample might be a strength in terms of clinical utility for biomarker discovery, 68,69 it also limits the ability to detect subtle differences between specific anxiety disorders. In addition, our cross-sectional, observational approach did not allow for causal inference.…”
Section: Limitationsmentioning
confidence: 99%